Urban living labs as innovation infrastructure for local urban intervention acceleration and student social learning: the impacts on community wellbeing in Heerlen - Blezer, Stefano; Abujidi, Nurhan; Sap, Herwin (Frontiers in Public Health, 2024)
See Revised version